Simbiosis: Consideraciones terminológicas y evolutivas (ING) - Hilje, Luko (Uniciencia, 1984)
The current types os symbiotic associations are redefined, based upon conceptual and biological considerations. A preliminary scheme of classification is presented, comprising two categories of symbiosis: reciprocal and antagonistic. The first one shows a single evolutionary line leading to increasing specifity between the partners and includes commensalism, protocooperation, and mutualism. The latter shows three evolutionary lines, representing different degrees of specificity, and involves amensalism, predation and parasitism.